If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1) = 2x + 22 Reorder the terms: 2(-1 + 3x) = 2x + 22 (-1 * 2 + 3x * 2) = 2x + 22 (-2 + 6x) = 2x + 22 Reorder the terms: -2 + 6x = 22 + 2x Solving -2 + 6x = 22 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 6x + -2x = 22 + 2x + -2x Combine like terms: 6x + -2x = 4x -2 + 4x = 22 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 4x = 22 + 0 -2 + 4x = 22 Add '2' to each side of the equation. -2 + 2 + 4x = 22 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 22 + 2 4x = 22 + 2 Combine like terms: 22 + 2 = 24 4x = 24 Divide each side by '4'. x = 6 Simplifying x = 6
| 3000-36=7500 | | 5x+3(6x-9)=111 | | 62=56+48v-42 | | 2x+3+2-x=6 | | -172-11x=x+92 | | a+6=9+5a | | -5y-20=40 | | -3b-ac=c+4 | | 7.4x-9=7x+12 | | 7x+2(x+6)=93 | | 11x^2+3x-15=-5 | | 5x^2y^5+10x^3y^3= | | 2x-2y+150=180 | | 54(2z)=(z+7)24 | | -87-2x=53+8x | | -14x+18y=63 | | (3+2x)2=23+23 | | 4(x+4)+(7)=70 | | 7x+2(x+6)=94 | | y=3x^2-8x+15 | | -7-14=2x+3 | | -5y+20=40 | | 62=56+42v-6v-42 | | X^2=-6x-17 | | 30=x(3x*1) | | 90=6x+3(x+3) | | -95-8x=31-x | | 5u+11=91 | | 3m^2+2m-11=-6 | | 4(x+4)(7)=70 | | -3m=4m-15 | | 2(37)-9=x |